DUPLICATION OF URBAN PLANNING FUNCTIONS IN A NIGERIAN STATE: UNCOVERING THE CAUSALITY - Daramola, Oluwole; Olojede, Olorunfemi; Ojo, Akintayo; Olowoporoku, Oluwaseun (PLANNING MALAYSIA, 2017)
This study examines the duplication in urban planning functions in Osun State of Nigeria. Data for the study were sourced from questionnaire administered on the directors of all the 35 planning agencies in the state. Data collected include respondents’ characteristics and the operation of the planning agencies and these were analysed using frequency distribution. The study revealed that the agencies experienced conflict of interest and the reason for that was mostly jurisdictional. Also, the agencies seldom related with one another. The study concluded that the structure of urban administration in the state causes duplication of urban planning functions and recommends, among others, legislative changes in urban administration of the state and Nigeria.